CHARACTERISTICS OF PROFESSIONAL IDENTITY IN CENTRAL ASIAN CITIES IN THE VIII - XII CENTURIES (Scientific journal of the Fergana State University, 2023)
Тis article discusses the changes related to handicrafts in the identities of the people of the region, especially their professional identities, during the period from the spread of Islam in Central Asia to the developed Middle Ages. For nearly five hundred years, it has been analyzed that the indigenous peoples of the major cities of Central Asia, especially the artisans, brought handicrafts to a new level by adapting ancient local and Islamic traditions to the new ideology.